A Rapid Intertidal Megafauna Survey Method Applied to Upogebia pugettensis, and Its Introduced Parasite, Orthione griffensis. Issue 3 (1st May 2014) - Chapman, John W.; Carter, Cameron S.
Abstract: Declines or extinctions of the native northeast Pacific intertidal blue mud shrimp, Upogebia pugettensis (Dana, 1852), over the species range are directly associated with intense infestations by the introduced Asian bopyrid isopod parasite, Orthione griffenis Markham, 2004 . Single point sampling sites and anecdotal records poorly resolve how this interaction occurs within estuaries and among geographical regions. This broad scale interaction can only be resolved at the meta-population scales over which they occur but the surveys needed for this research are proceeding slowly or, in most cases, have not begun. The large efforts and major field and computational resources that grid or random point surveys employed for this work to date have proven to be major obstacles. We therefore tested a new method in Alsea Bay, Oregon, in which shrimp bed perimeters and areas are algebraically defined previous to direct sampling within predefined population areas. This new method is intuitive, reduces logistics, greatly reduces field and computational resources and produces equally useful results to previous survey methods. The Alsea Bay populations of U. pugettensis surveyed by these new methods are sufficiently abundant to remain "ecosystem engineers." However, intense infestations of their populations by Orthione cause significant reproductive losses. The Alsea Bay population appears to be declining along with all other known U. pugettensis in Oregon estuaries.